Effects of Sc(Zr) on the microstructure and mechanical properties of as-cast Al–Mg alloys. Issue 6 (13th April 2017) - Pan, D.; Zhou, S.; Zhang, Z.; Li, M.; Wu, Y.
Abstract : Both the addition of 0.6% Sc and simultaneous addition of 0.2% Sc and 0.1% Zr exerted a remarkable effect on grain refinement of as-cast Al–Mg alloys, changing typical dendritic microstructure into fine equiaxed grains. Such effect was found to be related to the formation of primary particles, which acted as heterogeneous nucleation sites for α -Al matrix during solidification. Primary particles formed in Al–Mg–Sc–Zr alloy could be identified as the eutectic structure consisting of multilayer of 'Al3 (Sc, Zr) +  α -Al + Al3 (Sc, Zr)', with a 'cellular-dendritic' mode of growth. In addition, an attractive comprehensive property of as-cast Al–5Mg alloy due to the addition of 0.2% Sc and 0.1% Zr was obtained.